(untitled) (ENTHYMEMA, 2020)
In the present essay the author proposes a thematic and genre analysis of the new novel by the Russian writer Oleg Zobern, Autobiography of Jesus Christ, in the light of the most recent trends and cultural attitudes of contemporary Russian literature.